The Use Of Know, Want To Know, Learned (KWL) Technique To Improve Teaching And Learning Process. - Pancarini Dyah Rahayuningsih (Jurnal Pendidikan Edutama, 2014)
The Use of Know, Want to Know, Learned (KWL) Technique to Improve Teaching and Learning Process. This research aims at finding out whether KWL technique can improve the class situation when it is used in the teaching and learning process the class.The subject of the research was the first grade of SMA N 3 Sragen, Central Java, in the academic year of 2011/2012. The research was conducted in two cycles: the first cycle consisted of three meetings, and so did the second cycle. The procedures of the research consisted of planning, acting, observing, and reflecting. To collect the data the writer used class observation and made the conclusion to analyze the qualitative data.The result of the research shows that KWL technique can enhance class situation, in terms of: (a) the students’ attention that make them concentrate on the lesson; (b) their  participation and interaction when having and responding teacher’s questions; and (c) the motivation to join the teaching and learning process in the class.The research comes to the conclusion that there are some improvements of the students’ participation in teaching and learning process when using the KWL technique. Keywords: KWL technique, teaching learning process, class situation.